Current Status of Reflection and Professional Competence Enhancement Among University Teachers - Xue, Jiang; Jing, Wu (Journal of Educational Research and Policies, 2025)
This study takes the current status of reflection among university teachers as a starting point, delving into the intrinsic relationship between teacher reflection and professional development. By employing a mixed-methods approach that combines qualitative and quantitative research, this study investigates the levels of reflection among university teachers and their influencing factors. The survey results indicate the following: 1. The overall level of reflection among university teachers is relatively good, but inconsistencies are observed across various dimensions (practical, cognitive, moral, emotional, metacognitive, critical). 2. The level of reflection among university teachers is significantly correlated with factors such as teacher burnout, autonomy, job performance, and trait coping styles. Finally, the study proposes recommendations on how to promote teacher professional development by improving the current state of reflection, aiming to provide theoretical support and practical guidance for the development of university teaching staff.